Plyometric exercise enhances twitch contractile properties but fails to improve voluntary rate of torque development in highly-trained sprint athletes - Zimmermann, H. B.; Costa, F. E.; Sakugawa, R.; MacIntosh, B.; Diefenthaeler, F.; Dal Pupo, J. (European Journal of Sport Science, 2022)
Purpose: The objective of this study was to evaluate a plyometric conditioning activity (3 sets of 5 countermovement jumps, [CA]) for twitch properties and voluntary knee extension. Methods: After a familiarization session, fourteen highly-trained sprint athletes, 12 men (23.25 ± 7.17 years) and 2 women (23.0 ± 2.8 years) performed 2 experiments, each in a randomized order (crossover design). In one experiment, the time-course of twitch contractile properties was evaluated with and without the previous CA at 2, min intervals to 10 min of recovery. In the second session, maximal voluntary knee extension was evaluated at the same recovery intervals, for control and experimental condition in random order. Results: Mixed-model ANOVA with Bonferroni post-hoc revealed significant differences between pretest and 2 min (p<0.01, ES=0.42) and 4 min (p<0.01, ES=0.20) for peak twitch torque of quadriceps femoris muscles confirming postactivation potentiation [PAP] at these times. Twitch rate of torque development (RTD) was significantly greater than pretest value only at 2 min (p < 0.01, ES=0.58) after the CA. Twitch contraction time and ½ relaxation time were not significantly difference from pretest values after the CA (p>0.05). No significant difference was observed for voluntary RTD following CA. Conclusion: The plyometric CA increased twitch peak torque and RTD consistent with PAP; however, there was no effect of CA on voluntary RTD of knee extension at any time after the plyometric CA. Even with PAP confirmed, we observed that the CA fails to improve isometric RTD of quadriceps femoris muscles.